Does Liquidity Risk Affect The Profitability Of Vietnamese Commercial Banks? Evidence From Panel Data Threshold Regression (Journal of Namibian Studies : History Politics Culture, 2023)
This article uses the Panel threshold regression model with a panel of 30 commercial banks in Vietnam over the 2009 – 2021 period to investigate the effect of liquidity risk on bank performance. The findings show that at a threshold of total assets of USD 27,28 billion, the impact of liquidity risk on bank performance proxied by ROA turns from negative to positive. In contrast, any size threshold in models where the dependent variable is ROE does not be found. The findings also show that the level of liquidity risk is more critical in determining the impact direction of liquidity risk on bank performance than state ownership. From the estimation and testing results, the authors propose several policy implications for banks with total assets exceeding and below the threshold, as well as suggesting further research directions.